CLUSTERING OF DRUG, COSMETIC, TRADITIONAL MEDICINE, AND FOOD CRIME VULNERABILITY IN EAST JAVA USING THE K-MEDOIDS ALGORITHM - Puspitasari, Ria; Mahmudah, Mahmudah; Indriani, Diah; Indawati, Rachmah; Ardianah, Eva (Universitas Airlangga, 2025)
Drug and Food crime vulnerability mapping is the process of identifying potential crimes based on investigation, news, and study analysis, including the results of supervision, intelligence, cyber, and information analysis. The purpose of this study is to classify the vulnerability of drug, cosmetic, traditional medicine, and food crime in East Java using the K-Medoids algorithm, as well as to see the development of the vulnerability of drug, cosmetic, traditional medicine, and food crime in East Java Province for 5 years from 2019 to 2023. The method used is the K-Medoids algorithm with the determination of the number of clusters using the Average Silhouette Width (ASW) method. The highest ASW value between 0.28447-0.61210 was obtained in clusters with 5 groups, namely very high, high, medium, low, and very low clusters. The results of the study show that from 2019 to 2023, as many as 12 regencies/cities have an increasingly vulnerable status, while 26 other regencies/cities have an increasingly safe status. The 12 regencies/cities that are increasingly vulnerable are Bangkalan Regency, Gresik Regency, Lamongan Regency, Nganjuk Regency, Pamekasan Regency, Pasuruan Regency, Ponorogo Regency, Sidoarjo Regency, Tuban Regency, Malang City, Probolinggo City, and Surabaya City. It is necessary to empower the community and intensify communication, provide education and disseminate information massively regarding the use of legal and safe Drugs and Food products, especially in areas with very high vulnerability.